Low Geo‐Effectiveness of Fast Halo CMEs Related to the 12 X‐Class Flares in 2002. Issue 6 (16th June 2020) - Schmieder, B.; Kim, R.‐S.; Grison, B.; Bocchialini, K.; Kwon, R.‐Y.; Poedts, S.; Démoulin, P.
Abstract: It is generally accepted that extreme space weather events tend to be related to strong flares and fast halo coronal mass ejections (CMEs). In the present paper, we carefully identify the chain of events from the Sun to the Earth induced by all 12 X‐class flares that occurred in 2002. In this small sample, we find an unusual high rate (58%) of solar sources with a longitude larger than 74°. Yet all 12 X‐class flares are associated with at least one CME. The fast halo CMEs (50%) are related to interplanetary CMEs (ICMEs) at L1 and weak Dst minimum values (more than −51 nT), while five (41%) of the 12 X‐class flares are related to solar proton events (SPEs). We conclude that (i) all 12 analyzed solar events, even those associated with fast halo CMEs originating from the central disk region, and those ICMEs and SPEs were not very geo‐effective. This unexpected result demonstrates that the suggested events in the chain (fast halo CME, X‐class flares, central disk region, ICME, and SPE) are not infallible proxies for geo‐effectiveness. (ii) The low value of integrated and normalized southward component of the interplanetary magnetic field ( B z * ) may explain the low geo‐effectiveness for this small sample. In fact, B z * is well correlated to the weak Dst and low auroral electrojet activity. Hence, the only space weather impact at Earth in 2002 we can explain is based on B z * at L1. Key Points: We discussed geo‐effectiveness of the 12 X‐class flare‐CMEs in 2002 based on the available observations They failed to evoke strong disturbances since weak interplanetary magnetic field southward components The usual solar proxies (complex active region, X‐class flare, and fast halo CME) are not sufficient to forecast geo‐effectivity in 2002